2012
DOI: 10.1152/ajprenal.00257.2012
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of endogenous kallistatin exacerbates renal and cardiovascular oxidative stress, inflammation, and organ remodeling

Abstract: Kallistatin (KS) levels are reduced in the kidney and blood vessels under oxidative stress conditions. To determine the function of endogenous KS in the renal and cardiovascular systems, KS levels were depleted by daily injection of anti-rat KS antibody into DOCA-salt hypertensive rats for 10 days. Administration of anti-KS antibody resulted in reduced KS levels in the circulation but increased levels of serum thiobarbituric acid reactive substances (an indicator of lipid peroxidation) as well as superoxide fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 46 publications
(69 reference statements)
1
47
0
Order By: Relevance
“…50 In salt-induced hypertensive rats, kallistatin therapy attenuated vascular and renal damage, and reduced oxidative stress and inflammation, 38,51 while depletion of endogenous kallistatin augmented organ injury, and accentuated oxidative stress, inflammation and fibrosis. 54 In addition, kallistatin treatment dramatically improved survival and reduced inflammation, oxidative stress, apoptosis and organ damage in mice with polymicrobial sepsis and endotoxemia. 40,52,53 Mechanistically, kallistatin inhibits vascular inflammation by interacting with the transcription factor Kruppel-like factor 4 (KLF4), leading to increased eNOS expression and NO levels in endothelial cells.…”
Section: Kallistatin Is a Unique Anti-inflammatory Agentmentioning
confidence: 99%
“…50 In salt-induced hypertensive rats, kallistatin therapy attenuated vascular and renal damage, and reduced oxidative stress and inflammation, 38,51 while depletion of endogenous kallistatin augmented organ injury, and accentuated oxidative stress, inflammation and fibrosis. 54 In addition, kallistatin treatment dramatically improved survival and reduced inflammation, oxidative stress, apoptosis and organ damage in mice with polymicrobial sepsis and endotoxemia. 40,52,53 Mechanistically, kallistatin inhibits vascular inflammation by interacting with the transcription factor Kruppel-like factor 4 (KLF4), leading to increased eNOS expression and NO levels in endothelial cells.…”
Section: Kallistatin Is a Unique Anti-inflammatory Agentmentioning
confidence: 99%
“…Previous studies showed that KS may function independently of its interaction with kallikrein, such as lowering blood pressure and inhibiting angiogenesis and tumor growth (14)(15)(16)(17). Recent reports showed a novel role of KS in protection against ischemia-reperfusion myocardial and salt-induced renal and cardiovascular injuries by preventing apoptosis, oxidative stress, and inflammation (18)(19)(20). Studies in inflammatory bowel disease and obesity indicated that KS was significantly decreased in patients with inflamed intestine and adiposity compared to noninflammatory controls (21,22).…”
mentioning
confidence: 99%
“…Local delivery of the kallistatin gene into rat heart enhances cardiac performance and atenuates inlammatory cell iniltration after acute myocardial ischemia/reperfusion (I/R) [41]. In salt-induced hypertensive rats, kallistatin therapy atenuates vascular and renal damage and reduces oxidative stress and inlammation [17,18], while depletion of endogenous kallistatin augments organ injury and accentuates oxidative stress, inlammation, and ibrosis [47].…”
Section: Kallistatin Is a Potent Anti-inlammatory Agentmentioning
confidence: 99%
“…Kallistatin administration by gene or protein delivery protects against the pathogenesis of hypertension, heart and kidney damage, arthritis, inluenza virus infection, tumor growth, and metastasis in animal models [15][16][17][18][19][41][42][43][44][45][46]. Conversely, depletion of endogenous kallistatin by neutralizing antibody injection exacerbates cardiovascular and renal injury in hypertensive rats [47]. These indings indicate that kallistatin modulates a wide spectrum of biological activities, such as blood pressure, inlammation, multiorgan injury, and cancer.…”
Section: Introductionmentioning
confidence: 97%